Authors and affiliations - Omid Sadatpour; Mohammad Taha Ebrahimi; Maryam Akhtari; Nooshin Ahmadzadeh; Mahdi Vojdanian; Ahmadreza Jamshidi; Elham Farhadi; Mahdi Mahmoudi (BMC Musculoskeletal Disorders, 2022)
Abstract Background Ankylosing spondylitis (AS) is an inflammatory autoimmune disease that mostly affects different joints of the body. Macrophages are the predominant cells that mediate disease progression by secreting several pro-inflammatory mediators. Different receptors are involved in macrophages’ function including the adenosine receptors (AR). Our main objective in this study was to assess the effect of applying A2A adenosine receptor agonist (CGS-21,680) on the gene expression of inflammatory mediators including bone morphogenetic proteins (BMP)-2, 4 and matrix metalloproteinases (MMP)-3, 8, 9, and 13 on the macrophages from AS patients compared to healthy macrophages. Methods Monocytes were isolated from the whole blood of 28 individuals (AS patients and healthy controls in a 1:1 ratio). Macrophages were differentiated using macrophage colony-stimulating factor (M-CSF), and flow cytometry was performed to confirm surface markers. CGS-21,680 was used to treat cells that had been differentiated. Using SYBR green real-time PCR, relative gene expression was determined. Results Activating A2AAR diminished MMP8 expression in healthy macrophages while it cannot reduce MMP8 expression in patients’ macrophages. The effect of A2AAR activation on the expression of BMP2 and MMP9 reached statistical significance neither in healthy macrophages nor in the patients’ group. We also discovered a significant positive connection between MMP8 expression and patient scores on the Bath ankylosing spondylitis functional index (BASFI). Conclusion Due to the disability of A2AAR activation in the reduction of MMP8 expression in patients’ macrophages and the correlation of MMP8 expression with BASFI index in patients, these results represent defects and dysregulations in the related signaling pathway in patients’ macrophages.